Hydrogen: Fuel of the near future - Reddy, S.N. (Elsevier, 2020)
The continuous emissions of greenhouse gases from the consumption of fuels have a severe impact on the environment. This has created interest in hydrogen as a superior fuel that has tremendous energy density and generates water upon combustion. Hydrogen finds applications in several sectors such as transportation, industry, power generation, as well as heating and cooling of buildings, to name a few. A typical hydrogen-powered system comprises of production, storage, and delivery steps. This chapter presents an overview of hydrogen as a next-generation fuel followed by its present economy. A detailed discussion of different production routes, including thermochemical, hydrothermal, and biological techniques, has been presented. The feasibility and sustainability of the hydrogen fuel market based on the economics, social, technical, and environmental parameters including production resources and conversion techniques have been presented. The storage and transportation of hydrogen in different forms for its end-use applications have been outlined. The commercial applications, especially in motor transport and the progress, achieved to date have been highlighted. Moreover, the superiority of fuel cell vehicles over conventional engines in terms of performance and emissions has been discussed. Furthermore the potential to implement hydrogen in combination with the existing engines and hybrid fuel ignition systems that can power up the locomotive vehicles is detailed in this chapter. Â© 2020 Elsevier Inc. All rights reserved.